The mediating effect of opportunity for entrepreneurial activity on Micro-credit and women entrepreneur’s performence: a conceptual framework - Razli Che Razak; Isidore Ekpe; Norsiah Mat (2011)
Women enterprises aid grass root economic development of a country and women entrepreneurs contribute to the economic development of their families. However, it is discovered that women entrepreneurs perform below their male counterparts. This is caused by factors that normally affect entrepreneurship development, among which is lack of credit. Numerous evidence from the literature support the fact that women entrepreneurs’ lack of business capital and inability to access credit for business are occasioned by factors such as poverty, unemployment, low household and business income, lack of asset collateral, and societal discriminations mostly in developing countries. This leads to their low business performance, whereas the rate of their participation in the informal sector of the economy is higher than males, and credit could have positive effect on enterprise performance. However, the availability of credit could not lead to business performance without an opportunity for entrepreneurial activity because, Entrepreneurship and Financial Management Theorists believe that funds are mostly sourced to start or improve business, or to finance a predetermined project or contract. The objective of this study is to examine the mediating effect of opportunity for entrepreneurial activity on credit and women entrepreneurs’ performance. The study involves a survey using structured questionnaire and an in-depth interview to solicit responses from women entrepreneurs, and secondary data from microfinance institutions. Data analysis involves the use of descriptive statistics.